2013
DOI: 10.1371/journal.pone.0077460
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Semicarbazones, Thiosemicarbazones and Triazine Nitriles as Inhibitors of Leishmania mexicana Cysteine Protease CPB

Abstract: Cysteine proteases of the papain superfamily are present in nearly all eukaryotes. They play pivotal roles in the biology of parasites and inhibition of cysteine proteases is emerging as an important strategy to combat parasitic diseases such as sleeping sickness, Chagas’ disease and leishmaniasis. Homology modeling of the mature Leishmania mexicana cysteine protease CPB2.8 suggested that it differs significantly from bovine cathepsin B and thus could be a good drug target. High throughput screening of a compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 60 publications
0
36
0
Order By: Relevance
“…The recombinant cathespin L-like rCPB2.8 from L. mexicana is an isoform without the C-terminal extension that has been used as target in the search for new leishmanicidal compounds (Alves et al, 2001;Desai et al, 2006;Gontijo et al, 2012;Judice et al, 2013;Schröder et al, 2013;Steert et al, 2010). The structure of this enzyme has the amino acid residues Asn 60 , Asp 61 and Asp 64 in the α-helices (wall of the active site), and previous NMR experiments revealed that rCPB2.8 adopts a type of immunoglobulin-like fold (Juliano et al, 2004;Smith et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The recombinant cathespin L-like rCPB2.8 from L. mexicana is an isoform without the C-terminal extension that has been used as target in the search for new leishmanicidal compounds (Alves et al, 2001;Desai et al, 2006;Gontijo et al, 2012;Judice et al, 2013;Schröder et al, 2013;Steert et al, 2010). The structure of this enzyme has the amino acid residues Asn 60 , Asp 61 and Asp 64 in the α-helices (wall of the active site), and previous NMR experiments revealed that rCPB2.8 adopts a type of immunoglobulin-like fold (Juliano et al, 2004;Smith et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Structures of thiochroman-4-ones ( [1][2][3][4][5] and hydrazone derivatives (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). …”
Section: Methodsmentioning
confidence: 99%
“…In addition, numerous hydrazones have been reported to possess interesting biological activities such as antitumoral, antiviral and antiparasitic effects [8][9][10]; some hydrazones also exhibit activity against the parasites that cause malaria, leishmaniasis and Chagas disease [3,[11][12][13][14][15][16][17][18], where the inhibition of proteases and represent the most common mechanism of action for the hydrazones [16,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…[5] In view of that, and in the absence of an effective vaccine, there is a continuous interest in the identification of new drug targets and the development of new drug candidates for the treatment of this disease. [10] Nevertheless, to the best of our knowledge, only a few reports describe the identification of novel CPBs inhibitors, [6,11,12] such as natural compounds (e.g., morelloflavones), [13] metal complexes, [14] and electrophilic warhead-based compounds (α-ketoheterocycles, thiosemicarbazones, semicarbazones, nitriles, aziridinyl peptides) [15][16][17] that covalently bind the cysteine thiolate of the active site, thereby inactivating the enzyme. [7,8] It is well known that the parasite cysteine proteases (CPs) are druggable targets as they are considered crucial for the survival and infectivity of Leishmania in its human host.…”
Section: Introductionmentioning
confidence: 99%